SaraNextGen.Com

 $\quad y=A e^{m x}+B e^{-m x},$ where $A, B$ and $m$ are constants, is a solution of

(A) $\quad \frac{d^{2} y}{d x^{2}}-m^{2} y=0$
(B) $\quad A \frac{d^{2} y}{d x^{2}}+m^{2} y=0$
(C) $\quad B \frac{d^{2} y}{d x^{2}}+A y=0$
(D)$\frac{d^{2} y}{d x^{2}}+m y=m^{2}$



Question ID - 155367 | SaraNextGen Top Answer

 $\quad y=A e^{m x}+B e^{-m x},$ where $A, B$ and $m$ are constants, is a solution of

(A) $\quad \frac{d^{2} y}{d x^{2}}-m^{2} y=0$
(B) $\quad A \frac{d^{2} y}{d x^{2}}+m^{2} y=0$
(C) $\quad B \frac{d^{2} y}{d x^{2}}+A y=0$
(D)$\frac{d^{2} y}{d x^{2}}+m y=m^{2}$

1 Answer
127 votes
Answer Key / Explanation : (A) -

(A) $\quad \frac{d^{2} y}{d x^{2}}-m^{2} y=0$

127 votes


127